Asymmetric Reproductive Barriers and Gene Flow Promote the Rise of a Stable Hybrid Zone in the Mediterranean High Mountain - Abdelaziz, Mohamed; Muñoz-Pajares, A. Jesús; Berbel, Modesto; García-Muñoz, Ana; Gómez, José M.; Perfectti, Francisco (Frontiers in Plant Science, 2021)
Hybrid zones have the potential to shed light on evolutionary processes driving adaptation and speciation. Secondary contact hybrid zones are particularly powerful natural systems for studying the interaction between divergent genomes to understand the mode and rate at which reproductive isolation accumulates during speciation. We have studied a total of 720 plants belonging to five populations from two Erysimum (Brassicaceae) species presenting a contact zone in Sierra Nevada Mountains (SE Spain). The plants were phenotyped in 2007 and 2017, and most of them genotyped the first year using 10 microsatellites markers. Plants coming from natural populations were grown in a common garden to evaluate the reproductive barriers between both species by means of controlled crosses. All the plants used for the field and greenhouse study were characterized by measuring traits related to plant and flower size. We estimated the genetic molecular variances, the genetic differentiation, and the genetic structure by means of F-statistics and Bayesian inference. We also estimated the amount of recent gene flow between populations. We found a narrow unimodal hybrid zone where the hybrid genotypes appear to have been maintained by significant levels of unidirectional gene flow coming from parental populations and weak reproductive isolation between them. Hybrid plants exhibited intermediate or vigorous phenotypes depending on analyzed trait. The phenotypic differences between hybrid and parental plants were highly coherent between the field and controlled crosses experiments and through the time. The highly coherent results obtained by combining field, experimental and genetic data demonstrate the existence of a stable and narrow unimodal hybrid zone between E. mediohispanicum and E. nevadense at the high elevation in the Sierra Nevada Mountains.